ANALYSIS OF RADIONUCLIDE IN SURFACE SOIL SAMPLE - Chevy Cahyana (Buletin Limbah, 2007)
Radioactive effluent that released to environment may influence the population externally and internally. In order to protect population from the impact of radiation hazard, environmental radionuclide concentration must be monitored periodically. Analysis of radionuclide in surface soil sample is one of the environmental radionuclide monitoring programs task. Analyze of radionuclide that contain in surface soil sample from Higashi Ishikawa sampling point have been done. The analysis results show insignificant difference compared with theoretical estimations and the average of JAEA’s previous data. Radioactive effluent may be discharge to either the atmospheric or the aquatic environment. Radionuclide discharged to the atmosphere is dispersed due to normal atmospheric mixing processes. As they travel downwind, they irradiate the population externally and internally, the latter due to the inhalation of radionuclide from atmosphere. During their transport downwind radionuclide may be deposited from the atmosphere by impaction with the underlying surface or due to rain fall. This transfer onto land surface may lead to further irradiation of people by three important routes: external irradiation from deposited activity, internal irradiation from inhalation of re-suspended activity and ingestion of contaminated food. Liquid radioactive effluent may be discharged to fresh water (principally rivers), estuaries or marine environment. Radionuclide discharged to river is dispersed due to general water movement and sedimentation processes. The principal routes leading to the irradiation of people are external irradiation from sediment and internal irradiation due to ingestion of drinking water and food derived from the river, water used for irrigation of crops and pasture [1]. Man-made radionuclide was released into the environment trough nuclear weapons testing during the 1950’s and 1960’s mainly. The maximum annual deposition of 90Sr and 137Cs were recorded in 1963. After that the deposition of radionuclide from atmosphere decreased, however, most radionuclide that were deposit on land has been retained in surface soil layers. Obtaining the migration rates of radionuclide in the surface soils layer and the transfer factor of the radionuclide from soils to the crops are very important for radiation dose estimation [2]. Environment and peoples must be protected from the impact of radiation hazard. For this reason, environmental radionuclide concentration must be monitored periodically. Radionuclide that contained in atmosphere, surface soil, river water, food stuff, seawater, etc. can be known by some analytical methods and procedures. Sampling for surface soils and food stuffs (leafy vegetables, polished rice and milk) were done at observation area and reference area. Observation area is monitoring area under five kilometers radius from JAEA nuclear facilities. Reference area is area outside of observation area that monitored in order to take comparing data. Sampling for near shore seawater was done at four sampling points. Two sampling points are located at north from JAEA, i.e. Kujihama (6.5 km) and Toyoura (23 km). Two others sampling points are located at south from JAEA, i.e. Ajigaura (6.5 km) and Otake (27.5 km). Sampling for offshore seawater and seabed sediment were done using Seikai monitoring ship. Seafood stuff is bought from fisherman. On this paper, discussion is limited on analysis of radionuclide in surface soil sample from Higashi Ishikawa sampling point. Surface soil sample from Higashi Ishikawa sampling point have been analyzed. There are three analytical methods for analysis of radionuclide in surface soil sample, i.e. gamma spectrometry analysis for 137Cs, oxalate precipitation for 90Sr analysis and ion exchange for 239,240Pu analysis. The analysis results are compared with JAEA’s previous data and also compared with theoretical estimation using data from UNSCEAR 2000 REPORT [3].